ISLAMIC EDUCATIONAL VALUES IN THE CAWISAN TRADITION OF PALEMBANG CITY: AN ETHNOGRAPHIC STUDY ON THE INTERNALIZATION OF AQIDAH, SHARIA, AND AKHLAK - Ariesi Apriyanti; Choirun Niswah; Fitri Oviyanti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the implementation process of the Cawisan tradition in Palembang City, identify the Islamic educational values contained within it, and analyze its impact on the community's social behavior. This research employs a qualitative approach with an ethnographic design. The study was conducted in the areas of Tangga Buntung, Kertapati (Kemas Rindo), and Seberang Ulu II (11 Ulu) in Palembang City. Data collection techniques included participant observation, in-depth interviews, and documentation. Data analysis utilized the Miles and Huberman interactive model through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that the Cawisan tradition is a form of local wisdom-based Islamic education that continues to persist amidst the modernization of urban society. This tradition is carried out through book recitations (kitab studies), tausiyah (religious lectures), remembrance of God, and religious discussions held alternately in mosques and residents' homes. The internalized Islamic educational values include aqidah (creed) values in the form of strengthening tawhid (monotheism) and faith; sharia (Islamic law) values through the habituation of worship and Islamic muamalah (social transactions); and akhlak (morals) values through the cultivation of etiquette, social solidarity, and ukhuwah Islamiyah (Islamic brotherhood). Furthermore, the Cawisan tradition is proven to have a positive impact on changing the social behavior of the community, particularly in strengthening social care, enhancing interaction ethics, and serving as a social control amidst the challenges of the digital era. This research underscores that Cawisan is not merely a cultural tradition, but a non-formal Islamic educational institution relevant to building the character of modern society.